On some linyphiid spiders from Taiwan (Araneae: Linyphiidae) - Tanasevitch, Andrei V. (Zootaxa, 2011)
Seven linyphiid species are recorded from Taiwan, three of which are new: Maculoncus orientalis n. sp., Oreonetides taiwanus n. sp. and Tapinocyba formosa n. sp. Three species, Micrargus herbigradus (Blackwall, 1854), Oia imadatei (Oi, 1964) and Solenysa longqiensis Li & Song, 1992, are new to the Taiwanese fauna. Based on the new data, the linyphiid fauna of Taiwan is known to contain 20 linyphiid species.